Is the readability of abstracts decreasing in management research? - Lorenz Graf-Vlachy (Review of Managerial Science, 2021)
The readability of scientific texts is critical for the successful distribution of research findings. I replicate a recent study which found that the abstracts of scientific articles in the life sciences became less readable over time. Specifically, I sample 28,345 abstracts from 17 of the leading journals in the field of management and organization over 3~decades, and study two established indicators of readability over time, namely the Flesch Reading Ease and the New Dale–Chall Readability Formula. I find a modest trend towards less readable abstracts, which leads to an increase in articles that are extremely hard to read from 12% in the first decade of the sample to 16% in the final decade of the sample. I further find that an increasing number of authors partially explains this trend, as do the use of scientific jargon and corresponding author affiliations with institutions in English-speaking countries. I discuss implications for authors, reviewers, and editors in the field of management.
Keywords: 650; Readability; Management research; Replication; M100